Policy Analysis On Exclusive Breastfeeding for Informal Workers in Traditional Markets in North Sumatra - Peny Ariani; Nur Indrawaty Lipoeto; Eva Chundrayetti; Hema Malini; Adang Bachtiar; Delmi Sulastri; Mayetti Mayetti; Meri Neherta (Indonesian Journal of Global Health Research, 2024)
Most informal female workers in traditional markets are in the reproductive age range. One of the causes of low exclusive breastfeeding in women informal workers is the low implementation of policies related to exclusive breastfeeding in the workplace, especially in the informal sector. Objective to analyze the policies carried out by the local government related to exclusive breastfeeding policies for informal workers in traditional markets. Method: the study was qualitative with a phenomenological approach. Participants consisted of 12 employees of related agencies with purposive sampling. Data collection was done through in-depth interviews using voice records. Data analysis used content analysis by the collaizi method. The principle of traceability was applied to ensure rigor in the research. The results of this study obtained two themes related to the analysis of exclusive breastfeeding policies in Informal Workers of Traditional Markets in North Sumatra, namely 1) perception of lactation corner facilities in the markets; and 2) barriers to the certainty of lactation corners in the traditional market. It is essential to analyze the exclusive breastfeeding policy for informal workers in convention markets to create better policies by providing adequate lactation corner facilities for informal workers.